1992
DOI: 10.1021/jm00084a022
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterials. Synthesis and structure-activity studies of 3-aryl-2-oxooxazolidines. 4. Multiply-substituted aryl derivatives

Abstract: The synthesis and structure-activity relationship (SAR) studies of the effect of different polysubstitution patterns in the aromatic ring of 5-(acetamidomethyl)oxazolidinone antibacterials (I) on antibacterial activity are presented. Compounds I were prepared by the six-step synthesis described previously (Gregory, W. A.; et al. J. Med. Chem. [formula: see text] 1989, 32, 1673), electrophilic aromatic substitution reactions of 3-substituted compounds, and functional-group interchange reactions of 3,4-disubstit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 1 publication
2
38
0
2
Order By: Relevance
“…mp: 123. 5 oro-4-(4-thiomorpholinyl)phenyl]oxazolidine-2-one 9) (5.00 g, 14.8 mmol) in H 2 O : acetoneϭ1 : 4 (100 ml), 50% methyl morpholine N-oxide solution (10.0 ml, 440 mmol) and osmium tetroxide (3.77 g, 14.8 mmol) were added at room temperature. The reaction mixture was stirred at the same temperature for 10 min, then extracted with 1,2-dichloroethane, and the extract was washed with saturated sodium hydrosulfite solution, dried and concentrated to afford 11j (4 (S)-5-Aminomethyl-3-[3-fluoro-4-(4-methyl-1-piperidinyl)phenyl]oxazolidine-2-one (12d) A mixture of 11d (8.00 g, 24.0 mmol), triphenylphosphine (6.93 g, 26.4 mmol) and H 2 O (4.40 ml, 240 mmol) in THF (80 ml) was heated at 40°C for 11 h. After cooling, the reaction mixture was diluted with dilute hydrochloric acid and extracted with AcOEt.…”
Section: -Fluoro-4-(4-methyl-1-piperidinyl)aniline (8d)mentioning
confidence: 99%
See 1 more Smart Citation
“…mp: 123. 5 oro-4-(4-thiomorpholinyl)phenyl]oxazolidine-2-one 9) (5.00 g, 14.8 mmol) in H 2 O : acetoneϭ1 : 4 (100 ml), 50% methyl morpholine N-oxide solution (10.0 ml, 440 mmol) and osmium tetroxide (3.77 g, 14.8 mmol) were added at room temperature. The reaction mixture was stirred at the same temperature for 10 min, then extracted with 1,2-dichloroethane, and the extract was washed with saturated sodium hydrosulfite solution, dried and concentrated to afford 11j (4 (S)-5-Aminomethyl-3-[3-fluoro-4-(4-methyl-1-piperidinyl)phenyl]oxazolidine-2-one (12d) A mixture of 11d (8.00 g, 24.0 mmol), triphenylphosphine (6.93 g, 26.4 mmol) and H 2 O (4.40 ml, 240 mmol) in THF (80 ml) was heated at 40°C for 11 h. After cooling, the reaction mixture was diluted with dilute hydrochloric acid and extracted with AcOEt.…”
Section: -Fluoro-4-(4-methyl-1-piperidinyl)aniline (8d)mentioning
confidence: 99%
“…4) They also reported that there might be a small pocket around 3Ј-position on the benzene ring in the binding mode of 5-acetamide oxazolidinones. 5) While considering their suggestions, we focused our attention on lipophilicity to further study 5-thiocarbonyl oxazolidinones. Partition coefficient (log P), which is well known as an index of lipophilicity, is an important physicochemical parameter in the development of antibacterial agent because it is known to be closely related to the permeation through a lipid coat of bacteria.…”
mentioning
confidence: 99%
“…The acidic aqueous layer was washed with Et 2 O, neutralized with K 2 CO 3 , and then reextracted with Et 2 O. The ethereal extract was dried over anhydrous MgSO 4 and then evaporation of the solvent under reduced pressure afforded a solid material. This was treated with 10% methanolic HCl and concentrated under reduced pressure to give the crude product of 3.…”
Section: (Cooh)mentioning
confidence: 99%
“…4,5) These derivatives (3) are selected as the target heterocycles for one of the synthetic applications of the above unique amino acid b-aminoalanine derivatives (1) (Fig. 1).…”
mentioning
confidence: 99%
“…5,6) This paper deals with the relative rates of ring closure by cyclization with diethyl carbonate (EtO) 2 CO from aminoalcohols as starting material. We report here two typical experimental results for the cyclization that has two possibilities as a function of the ring intramolecular cyclization by (EtO) 2 CO.1…”
mentioning
confidence: 99%